Differential spatial distribution of hepatitis B virus by ethnicity in British Columbia, Canada: Expanded role of a large administrative cohort. (2018) - Butt, Zahid; Janjua, Naveed; Wong, Stanley; Yu, Amanda; Alvarez, Maria; Chapinal, Nuria; Wong, Jason; Binka, Mawuena; Buxton, Jane; Gilbert, Mark; Darvishian, Maryam; Rossi, Carmine; et al.
No abstract available